An interleukin 6‐based genetic risk score strengthened with interleukin 10 polymorphisms associated with long‐term kidney allograft outcomes. (1st December 2022) - Eskandari, Siawosh K.; Gaya da Costa, Mariana; Faria, Bernardo; Petr, Vojtech; Azzi, Jamil R.; Berger, Stefan P.; Seelen, Marc A. J.; Damman, Jeffrey; Poppelaars, Felix
Abstract : Of all kidney transplants, half are still lost in the first decade after transplantation. Here, using genetics, we probed whether interleukin 6 (IL‐6) could be a target in kidney transplantation to improve graft survival. Additionally, we investigated if a genetic risk score (GRS) based on IL6 and IL10 variants could improve prognostication of graft loss. In a prospective cohort study, DNA of 1271 donor‐recipient kidney transplant pairs was analyzed for the presence of IL6, IL6R, IL10, IL10RA, and IL10RB variants. These polymorphisms and their GRS were then associated with 15‐year death‐censored allograft survival. The C|C‐genotype of the IL6 polymorphism in donor kidneys and the combined C|C‐genotype in donor‐recipient pairs were both associated with a reduced risk of graft loss ( p = .043 and p = .042, respectively). Additionally, the GRS based on IL6, IL6R, IL10, IL10RA, and IL10RB variants was independently associated with the risk of graft loss (HR 1.53, 95%‐CI [1.32–1.84]; p < .001). Notably, the GRS improved risk stratification and prediction of graft loss beyond the level of contemporary clinical markers. Our findings reveal the merits of a polygenic IL‐6‐based risk score strengthened with IL‐10‐ polymorphisms for the prognostication and risk stratification of late graft failure in kidney transplantation.